(untitled) (Clinics, 2012)
Surgical approaches to pancreatic endocrine tumors associated with multiple endocrine neoplasia type 1 may differ greatly from those applied to sporadic pancreatic endocrine tumors. Presurgical diagnosis of multiple endocrine neoplasia type 1 is therefore crucial to plan a proper intervention. Of note, hyperparathyroidism/multiple endocrine neoplasia type 1 should be surgically treated before pancreatic endocrine tumors/multiple endocrine neoplasia type 1 resection, apart from insulinoma. Non-functioning pancreatic endocrine tumors/multiple endocrine neoplasia type 1 >;1 cm have a high risk of malignancy and should be treated by a pancreatic resection associated with lymphadenectomy. The vast majority of patients with gastrinoma/multiple endocrine neoplasia type 1 present with tumor lesions at the duodenum, so the surgery of choice is subtotal or total pancreatoduodenectomy followed by regional lymphadenectomy. The usual surgical treatment for insulinoma/multiple endocrine neoplasia type 1 is distal pancreatectomy up to the mesenteric vein with or without spleen preservation, associated with enucleation of tumor lesions in the pancreatic head. Surgical procedures for glucagonomas, somatostatinomas, and vipomas/ multiple endocrine neoplasia type 1 are similar to those applied to sporadic pancreatic endocrine tumors. Some of these surgical strategies for pancreatic endocrine tumors/multiple endocrine neoplasia type 1 still remain controversial as to their proper extension and timing. Furthermore, surgical resection of single hepatic metastasis secondary to pancreatic endocrine tumors/multiple endocrine neoplasia type 1 may be curative and even in multiple liver metastases surgical resection is possible. Hepatic trans-arterial chemo-embolization is usually associated with surgical resection. Liver transplantation may be needed for select cases. Finally, pre-surgical clinical and genetic diagnosis of multiple endocrine neoplasia type 1 syndrome and localization of multiple endocrine neoplasia type 1related tumors are crucial for determining the best surgical strategies in each individual case with pancreatic endocrine tumors.